ANALISIS FAKTOR PENYEBAB KURANGNYA KEMAMPUAN SISWA DALAM BACA TULIS AL-QUR’AN DI MTsN KEDURANG BENGKULU SELATAN - - Gusman (Al-Bahtsu : Jurnal Penelitian Pendidikan Islam, 2017)
Problems faced  in  the  learning process  and  what  efforts  are  made  in  tackling  obstacles  in  learning to  read Al-Quran  in  MTs N Kedurang South  Bengkulu. In  this  study  data  collection is done  through interviews,  observation and  documentation, with  informants are  the  Head  of  School,  Waka  Curriculum and  Al-Qur’an  reading teacher in MTs Negeri  Kedurang. While  to  analyze  data  using  qualitative  descriptive  analysis technique, that  is descriptive  and menginterprestasikan data  that  have been  obtained so that  will depict  reality that  actually in accordance with existing phenomenon. The  results  of this study indicate Factors  that  inhibit  the  study of the  Koran  in accordance with among others:  (a)  Less fulfillment of books  and  supporting learning media  (b)  Minimnya  time  of religious  learning, especially the  Koran.  (C)  The  level of student ability varies. Problematic faced  by teachers are: a. Level of knowledge of students who are  not  the  same, b. The  limited  hours  of teaching, c. The  use of teaching methods in traditional learning makes students quickly bored. D. Evaluation  of the  affective and  psychomotor domains is rarely done  due  to limited  time  and facilities.  As for  efforts  to  improve  the  literacy  of Al-Qur’an  students are:  a. Increase hours  of recitation after  school hours  after  b. Conducting cooperation with TPA in  the  area  of  origin  of each  student. C. Creating good  conditions during the  teaching and  learning process.  D. Completing facilit i es and  infrastructure of learning Al-Qur’an  In  MTs Negeri  Kedurang